(untitled) (Research, Society and Development, 2022)
Over the years, Medicine has gone through different fields of action to offer health and prevention in a holistic way, encompassing different forms of health care. One of these fields is the so-called Regenerative Medicine, a promising area for health professionals who want to develop new solutions for the health of their patients. Regenerative medicine constitutes a shift from the conventional medical paradigm to a new one, which seeks to regenerate the organism at the cellular or tissue level. Taking into account the theme little used in dentistry, this scientific production sought to understand how regenerative medicine is available in dentistry, seeking to explore the history of regenerative medicine in Brazilian dentistry as well as to describe the available therapies as it points out the benefits in the treatment of patients submitted to therapies available today and in addition to discussing the limits of professional activity with regenerative medicine in Brazil. Method: integrative literature review of qualitative, explanatory and deductive literature; searches were carried out in digital databases: SciELO, PubMed and LILACS; in English and Portuguese, adhere to the theme and have been published in the curvature of time from 2002 to 2022. Results: we verified the use of synthetic materials (hydroxyapatite, chitosan and carbon nanotube compound) and biological materials (PRP, stem cells ), as well as the union of the two with the same purpose of regenerating the patient’s body and obtaining satisfactory results as reported by the OCT technique. We conclude that knowledge about regenerative medicine is vital in dentistry, for professionals and academics, together there is a need for more studies and records in the literature for professional guidance and advancement of methods.